Phosphorylation of the Chloroplastic Metalloprotease FtsH in Arabidopsis Characterized by Phos-Tag SDS-PAGE - Kato, Yusuke; Sakamoto, Wataru (Frontiers in Plant Science, 2019)
FtsH is an essential ATP-dependent metalloprotease for protein quality control in the thylakoid membrane of Arabidopsis thaliana chloroplasts. It is required for chloroplast development during leaf growth, and particularly for the specific degradation of photo-damaged D1 protein in the photosystem II (PSII) complex to maintain photosynthesis activity. In the thylakoid membrane, the reversible phosphorylation of proteins is known to control the activity and remodeling of photosynthetic complexes, and previous studies implicate that FtsH is also phosphorylated. We therefore assessed the phosphorylation status of FtsH and its possible role in the regulatory mechanism in this study. The phosphorylation level of FtsHs that compose the FtsH heterohexameric complex was investigated by phosphate-affinity gel electrophoresis using a Phos-Tag molecule. Phos-tag SDS-PAGE of thylakoid proteins and subsequent immunoblot analysis showed that both type A (FtsH1/5) and type B (FtsH2/8) subunits were separable into phosphorylated and non-phosphorylated forms. Neither different light conditions nor the lack of two major thylakoid kinases, STN7 and STN8, resulted in any clear difference in FtsH phosphorylation, suggesting that this process is independent of the light-dependent regulation of photosynthesis-related proteins. Site-directed mutagenesis of putatively phosphorylated Ser or Thr residues into Ala demonstrated that Ser-212 may play a role in FtsH stability in the thylakoid membranes. Different phosphorylation status of FtsH oligomers analyzed by two-dimensional clear-native/Phos-tag SDS-PAGE implied that phosphorylation partially affects FtsH complex formation or its stability.